2017
DOI: 10.1039/c6ra26759a
|View full text |Cite
|
Sign up to set email alerts
|

A solid polymer microneedle patch pretreatment enhances the permeation of drug molecules into the skin

Abstract: In this work, solid microneedles (MNs) for skin pretreatment were systematically studied including MN height, density, spacing, and so on.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(74 citation statements)
references
References 36 publications
4
63
0
1
Order By: Relevance
“…The mean normoglycemic time treated with 20 IU-insulin-loaded TMAP-II was approximately 11.63 h. This indicated that just two TMAPs could maintain the diabetic rats in the normoglycemic state for a day. To the best of our knowledge, this is the longest normoglycemic time period achieved with treatments using the insulin-loaded microneedle-based transdermal patches, as reported for type 1 diabetic rats (Chen et al., 2009 ; Zhou et al., 2010 ; Liu et al., 2012 ; Ling and Chen, 2013 ; Li et al., 2017b ; Yu et al., 2017a ; Yu et al., 2017b ; Yu et al., 2017c ). Therefore, 20 IU-insulin-loaded TMAPs administrated with approach II is an attractive candidate to treat type 1 diabetic SD rats.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…The mean normoglycemic time treated with 20 IU-insulin-loaded TMAP-II was approximately 11.63 h. This indicated that just two TMAPs could maintain the diabetic rats in the normoglycemic state for a day. To the best of our knowledge, this is the longest normoglycemic time period achieved with treatments using the insulin-loaded microneedle-based transdermal patches, as reported for type 1 diabetic rats (Chen et al., 2009 ; Zhou et al., 2010 ; Liu et al., 2012 ; Ling and Chen, 2013 ; Li et al., 2017b ; Yu et al., 2017a ; Yu et al., 2017b ; Yu et al., 2017c ). Therefore, 20 IU-insulin-loaded TMAPs administrated with approach II is an attractive candidate to treat type 1 diabetic SD rats.…”
Section: Resultsmentioning
confidence: 72%
“…the ability to create multiple insertions into the skin). The mechanical stability of TMAP can be evaluated by the relationship between the intact insertions and the microneedle number (Li et al., 2017b ). The red dots remained on the skin surface indicates the rhodamine B permeation into the skin through the microchannels created by solid MA, which means successful insertion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microneedle (MN) is a micrometer size array of needles which might be able to penetrate superficial dermis by enhancing permeability of skin, thereby, easy local and systematic administration of drugs with high drug delivery efficiency . The MN‐based insulin delivery studies reported in the literature mainly comprises solid MNs, hollow MNs, and dissolving MNs . Solid MNs are used to create transient channels on skin to facilitate insulin permeability, but lack the capacity to load drugs.…”
Section: Introductionmentioning
confidence: 99%